Ship to Belfast : European Artists create the new image of the city of Belfast : the image of the Northern Ireland Metropolis in a peaceful future. (Frankfurt am Main : Verein zur Förderung der Kunst im öffentlichen raum, 2001)
Catalyst Art Studio ; Collins, Phil ; Connolly, Brian ; Cybulska, Herbert ; d'Ailly, Stella ; Demski, Eva ; Fischer, Herbert ; Flax Art Studios ; Fursman, Joanna ; Hackett, Stephen ; Napier, Philip ; Hogg, Mike ; Hughes, Allen ; Kennedy, Brian ; Lessick, Helen ; Mac Donagh, Eileen ; MacLennan, Alastair ; Newport, Vivienne ; Richard, Peter ; Roelli, Ed ; Schedl, Gerhard ; Tranter, Neville ; McLiam Wilson, Robert
Engels
boek
Keywords: Belfast; Ierland